2019
DOI: 10.5380/rf.v50i1.61136
|View full text |Cite
|
Sign up to set email alerts
|

INFLUENCE OF ACICULAS DEPOSITION ON NATURAL REGENERATION IN SUB-WOODS OF Pinus taeda L. FOREST STAND

Abstract: This study was conducted in a commercial forest stand of Pinus taeda L. located in Curitibanos, in the State of Santa Catarina, Brazil. The objective of this study was to evaluate the influence of the physical barrier caused by the deposition of aciculas, on natural regeneration mechanisms of native species in sub-woods of P. taeda L. forest stand. Three plots (10 x 10 m) were installed in the sub-woods of the forest stand, and the natural regeneration was evaluated in the control (presence of aciculas) and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
1
2
1
Order By: Relevance
“…The production of seeds found at PAERC can be an important factor for invasive success of P. taeda. A similar pattern, in which a peak in seed rain occurs around the months of April/May, with year round seed rain has been found in other studies in the Atlantic Forest (Bechara et al 2013(Bechara et al , 2014Fockink et al 2020).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The production of seeds found at PAERC can be an important factor for invasive success of P. taeda. A similar pattern, in which a peak in seed rain occurs around the months of April/May, with year round seed rain has been found in other studies in the Atlantic Forest (Bechara et al 2013(Bechara et al , 2014Fockink et al 2020).…”
Section: Discussionsupporting
confidence: 87%
“…The annual volume of Pinus taeda seed dispersion found in this study (125,000 seeds/ha/year in EPI and 404,000 seeds/ha/year in EIV) is lower than that obtained by Bechara et al (2013; with 2 million Pinus elliotti seeds/ha/year, or that of Fockink et al (2020) with 750.000 Pinus taeda seeds/ha/year. However, studies in the literature have recorded seed rain values in areas adjacent to forestry stands where the density of P. taeda is higher than that found in PAERC.…”
Section: Discussioncontrasting
confidence: 82%
“…Our study shows that passive restoration is a promising alternative in logged pine plantations, even if factors like pine needles (Fockink et al 2019), or low levels of soil organic matter (Tulande et al 2018) are not manipulated. Likewise, it confirms that the main filter for natural recovery at pine plantations would be light availability (Baruch et al 2016).…”
Section: Discussionmentioning
confidence: 71%
“…However, there is no sufficient information about the role of macro and mesofauna groups in pine litter breakdown. Preview studies have shown the effects of Pinus species to understory plant species (FOCKINK et al, 2020) and soil invertebrates' community (ORTIZ et al, 2021) in pine plantation and invasions, which point impacts for ecosystems where Pinus spp. are non-native.…”
Section: Introductionmentioning
confidence: 99%